Bruise-like cutaneous lesions as the early presentation of blastic plasmacytoid dendritic cell neoplasm - Yi-Hsuan Chou; Ruey-Yi Lin; Meng-Sui Lee; Hsiao-Ping Wu; Che-Pin Lin; Chen-Yi Wu (Wolters Kluwer Medknow Publications, 2014)
Blastic plasmacytoid dendritic cell neoplasm (BPDCN) is a very rare and highly aggressive hematopoietic malignancy associated with a poor prognosis. It has been recognized to originate from precursors of plasmacytoid dendritic cells and has recently been established as a distinct entity. The most frequent clinical presentations are prominent skin lesions, followed by peripheral blood, bone marrow, and other organ involvement. Treatment outcomes are often disappointing due to a high relapse rate after chemotherapy and risk of leukemic dissemination. Herein, we report a case of BPDCN in a 41-year-old man who presented with cutaneous and nasopharyngeal lesions, and achieved a complete response after systemic chemotherapy. Dermatologists should be aware of BPDCN and its clinical presentations, as early diagnosis with appropriate treatment is crucial to improve its prognosis.